2012
DOI: 10.1183/09031936.00099812
|View full text |Cite
|
Sign up to set email alerts
|

Hypereosinophilic obliterative bronchiolitis: a distinct, unrecognised syndrome

Abstract: Biopsy-proven cases of eosinophilic bronchiolitis have only been reported in isolation, and all come from Japan.We present six patients with hypereosinophilic obliterative bronchiolitis (HOB), defined by the following criteria: 1) blood eosinophil cell count .1 G?L -1 and/or bronchoalveolar lavage eosinophil count .25%; 2) persistent airflow obstruction despite high-dose inhaled bronchodilators and corticosteroids; and 3) eosinophilic bronchiolitis at lung biopsy (n51) and/or direct signs of bronchiolitis (cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 33 publications
4
24
0
Order By: Relevance
“…The next step to exploit these new scenarios could be the collection of a significant number of patients with these clinical-radiological characteristics provided with pathological (and biological) data. In fact, CORDIER et al [1] reported histopathological information in only two patients. Interestingly, as the lesions are centrilobular, a bronchoscopic approach (transbronchial lung biopsy with common flexible forceps, jumbo forceps or even cryoprobes) could obviate the need of a surgical approach.…”
Section: Eosinophilic Bronchiolitis: Is It a New Syndrome?mentioning
confidence: 99%
See 4 more Smart Citations
“…The next step to exploit these new scenarios could be the collection of a significant number of patients with these clinical-radiological characteristics provided with pathological (and biological) data. In fact, CORDIER et al [1] reported histopathological information in only two patients. Interestingly, as the lesions are centrilobular, a bronchoscopic approach (transbronchial lung biopsy with common flexible forceps, jumbo forceps or even cryoprobes) could obviate the need of a surgical approach.…”
Section: Eosinophilic Bronchiolitis: Is It a New Syndrome?mentioning
confidence: 99%
“…In this issue of the European Respiratory Journal, a new distinct syndrome, hypereosinophilic obliterative bronchiolitis, is described by CORDIER et al [1]. This syndrome is defined by: 1) a blood eosinophil cell count .1 G?L -1 and/or a bronchoalveolar lavage (BAL) eosinophil differential cell count .25%; 2) persistent airflow obstruction on lung function tests not modifiable after 4-6 weeks of inhaled corticosteroid therapy (2000 mg?day -1 of beclometasone or equivalent); and 3) a lung biopsy showing inflammatory bronchiolitis with prominent bronchiolar wall infiltration by eosinophils and/or characteristic direct high-resolution computed tomography (HRCT) features of bronchiolitis (poorly defined centrilobular nodules, branching opacities and tree-inbud pattern).…”
Section: Eosinophilic Bronchiolitis: Is It a New Syndrome?mentioning
confidence: 99%
See 3 more Smart Citations